1997
DOI: 10.1177/106002809703100706
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Prescription Medicines in Southwestern France

Abstract: These results show the efficiency of a method for detecting falsified prescriptions forms using community pharmacists. The abuse of medicines already known for their addictive potential can be estimated and alerts can also be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…The data are also consistent with a number of epidemiological and case report studies worldwide demonstrating buprenorphine abuse (O'Connor et al, 1988;Sakol et al, 1989;Singh et al, 1992;Baumevieille et al, 1997). It is important to note, however, that the present study was conducted in nondependent individuals.…”
Section: Discussionsupporting
confidence: 77%
“…The data are also consistent with a number of epidemiological and case report studies worldwide demonstrating buprenorphine abuse (O'Connor et al, 1988;Sakol et al, 1989;Singh et al, 1992;Baumevieille et al, 1997). It is important to note, however, that the present study was conducted in nondependent individuals.…”
Section: Discussionsupporting
confidence: 77%
“…Another study in France found that 27% of IDUs were exclusively buprenorphine injectors, while another 37% reported polydrug use [112]. Some of these IDUs purchased their buprenorphine from individuals with a prescription [113], while others obtained it by altering or forging prescriptions [51,114,115]. Similar results were provided by Obadia et al [116].…”
Section: European Studiessupporting
confidence: 76%
“…The abuse potential of buprenorphine, which has been demonstrated in experimental and clinical settings [48][49][50], is generally considered to be less than that of full opioid agonists [51,52]. Buprenorphine can cause euphoria [53,54], although to a lesser degree than full opioid agonists [31,[53][54][55], and has reinforcing effects, again to a lesser degree than full opioid agonists [56][57][58][59][60][61][62].…”
Section: Routes Of Administrationmentioning
confidence: 99%
“…The principle of data collection of falsified prescriptions in the community pharmacy setting has been previously tested in Sweden [8,9] and France [10,11,12]. The results of these experiences suggest that these surveys can be used to advantage in drug abuse monitoring systems as additional ways of identifying signs of abuse [9,13,14,15].…”
Section: Introductionmentioning
confidence: 94%